Relationship between sheep feces scores and gastrointestinal microorganisms and their effects on growth traits and blood indicators - Yang, Xiaobin; Wang, Jianghui; Cheng, Jiangbo; Zhang, Deyin; Huang, Kai; Zhang, Yukun; Li, Xiaolong; Zhao, Yuan; Zhao, Liming; Xu, Dan; Ma, Zongwu; Liu, Jia; et al. (Frontiers in Microbiology, 2024)
Fecal scores are crucial for assessing the digestive and gastrointestinal status of animals. The Bristol fecal scoring system is a commonly used method for the subjective evaluation of host feces, there is limited research on fecal scoring standards for fattening Hu sheep. In this study, Hu sheep were collected for rumen, rectum, and colon contents for 16S rDNA sequencing. 514 Hu sheep feces were scored based on the Bristol fecal scoring system, and production performance at each stage was measured. Finally, we developed the scoring standard of the manure of Hu sheep in the fattening period (a total of five grades). The result shows that moisture content significantly increased with higher grades (p < 0.05). We analyzed the relationship between fecal scores and production traits, blood indices, muscle nutrients, and digestive tract microorganisms. The growth traits (body weight, body height, body length, average daily gain (ADG), and average daily feed intake (ADFI) during 80–180 days), body composition traits of the F3 group, and the carcass traits were found to be significantly higher (p < 0.05) than those of the F1 and F2 groups. There was no significant difference in gastrointestinal microflora diversity among all groups (p > 0.05). Significant differences were observed in Aspartate aminotransferase, Glucose, Total bilirubin, and Red Blood Cell Count between groups (p < 0.05). The mutton moisture content in group F4 was significantly higher than in the other groups, and the protein content was also the lowest (p < 0.05). The results of the correlation analysis demonstrated that Actinobacteria, Peptostreptococcaceae, Acidaminococcales, Gammaproteobacteria, and Proteobacteria were the significant bacteria affecting fecal scores. In addition, Muribaculaceae and Oscillospiraceae were identified as the noteworthy flora affecting growth performance and immunity. This study highlights the differences in production traits and blood indicators between fecal assessment groups and the complex relationship between intestinal microbiota and fecal characteristics in Hu sheep, suggesting potential impacts on animal performance and health, which suggest strategies for improved management.